A quasi-experiment on the effectiveness of cardiac rehabilitation in quality of life of cardiac patients with the caregivers’ involvement - Rajen Durai, Ruthpackiavathy; Idris, Khairuddin; Maskon, Oteh; Romli, Muhammad Hibatullah; Abdul Razak, Najibah (Academy of Health Professionals, 2021)
Introduction: Coronary Heart Disease can result in impaired quality of life which can inhibit an early recovery with successful outcomes for cardiac patients. Objective: To investigate the effect of a structured cardiac education and early intervention cardiac rehabilitation program on quality of life in cardiac patients involving caregivers. Method: A quasi experimental study with a purposive sampling was carried out where 132 acute coronary syndrome patients hospitalized for treatment were recruited and allocated to the experiment and control group with and without caregivers. A structured educational intervention and cardiac rehabilitation was initiated for the experimental group with and without caregivers. The outcome was measured using the World Health Organization Quality Of Life-BREF (WHOQOL-BREF) instrument.Results: Data was measured with repeated measures ANOVA between baseline, discharge and follow-up between the intervention and control group with p<0.05 There was a statistically significant difference in QOL in both the groups with and without caregivers in the following domains: psychological health (F=3.784, p=0.002); social relationship (F=4.267, p=0.000) and environment (F=3.578, p=0.004). There was not a statistically significant difference between both the groups in the physical health domain (F=1.316, p=0.266).Conclusion: The results indicated that a structured cardiac educational intervention and cardiac rehabilitation with the involvement of the caregivers have significant effects on the quality of life of cardiac patients. The findings provide useful evidence to improve health outcomes of acute coronary syndrome patients involving the caregivers.